Les rapports femmes-hommes en milieu urbain: patriarcat ou partenariat ? - Villeneuve, Paul (Cahiers de géographie du Québec, 1991)
The paper first shows, in the context of recent theorising on hierarchies and markets, the existence of relationships between increasing female labour force participation and the emergence of certain forms of urban social polarisation. These new forms of polarisation are then linked with occupational asymmetry within employed couples. This analysis tends to suggest that central city neighbourhoods are milieux more conducive to the erosion of patriarchy than suburbs. Finally, the question of a new gender partnership is suggested to be as crucial to the theorising on local development than that of class partnership.